Land exchange, a lever for the agroecological transition of livestock farming? - Timothée Fouqueray; Alexandra Langlais; Thomas Houet (Cybergeo)
Agriculture both contributes to and suffers from climate disruptions and biodiversity loss. To address these challenges, agricultural practices are evolving, particularly through the agroecological transition, which integrates agronomic and ecological knowledge. However, the land-use dimension – specifically parcel distribution – remains underexplored in research, despite its crucial role in this transition. This article examines the benefits and limitations of farmland exchanges in reducing greenhouse gas emissions, preserving biodiversity-friendly habitats, and improving farmers' working conditions. It is based on an analysis of dairy farming in the Zone Atelier Armorique, drawing on interviews with (para-)public agencies responsible for agricultural land management in Ille-et-Vilaine. Combining insights from ecology, geography, and law, the study first highlights how land exchanges support farmers, enhance carbon storage, and benefit species dependent on agricultural landscapes. It then evaluates the various farmland exchange mechanisms available to farmers, assessing their implications for both agricultural livelihoods and environmental sustainability. Finally, the article explores the efficiency, effectiveness, and alignment of land exchanges with territorial agri-environmental policies, positioning them within a systemic, long-term vision of the agroecological transition. The conclusion underscores the need to mobilize multiple land law instruments—including land reserves – and to allocate dedicated funding within agroecological transition budgets. This would support the long-term facilitation of land exchanges by agricultural and environmental organizations.Keywords: agriculture, land politics, sustainability, grazing, spatial practices